KAJIAN POTENSI AGRBISNIS HUB DALAM MENINGKATKAN NILAI TAMBAH SEKTOR PERTANIAN DI KABUPATEN KOLAKA - Kabupaten Kolaka, Balitbang; Rizaldi Makmur, Muhammad; Lapau, Fitri; Sofian Maksar, Muhammad; Hamid, Nisrina (JIEM : Journal Of International Entrepreneurship And Management, 2024)
Agribusiness is a business based on agricultural business or other fields that support it, both upstream and downstream sectors that refer to the main view that agribusiness works on the food sector chain (food supply chain) in other words, agribusiness is an economic perspective for food supply businesses. This study aims to assess the potential of agribusiness hubs in increasing the added value of the agricultural sector in Kolaka Regency which consists of identifying agribusiness products, economic and institutional infrastructure profiles and formulating pre-feasibility of Agribusiness in Kolaka Regency. The research method used is a qualitative approach and the results obtained show that Kolaka Regency has several commodities that have potential as agribusiness hub commodities in the food crop, horticulture and plantation sectors. The economic and institutional infrastructure of farmers as part of the Agribusiness Hub support system still faces obstacles, such as limited access to marketing, financing, and digital literacy. The implementation of the Agribusiness Hub model recommended in this study is the Managing Agency approach.